Environmental, social, and governance (ESG) factors and firm value: A systematic literature review of theories and empirical evidence - Bani-Khaled, S.; Azevedo, G.; Oliveira, J. (AMS Review, 2025)
This systematic literature review critically examines the theoretical frameworks and empirical evidence linking Environmental, Social, and Governance (ESG) factors to firm value by analysing 75 studies published between 2015 and 2023 from the Scopus database. Employing a PRISMA-based methodology, this review identifies dominant theories—including Stakeholder, Agency, and Legitimacy theories—that explain the varied impacts of ESG on firm value. The evidence suggests that ESG integration generally enhances corporate reputation and performance; however, these effects are highly context-specific and influenced by regional, sectoral, and governance variations. Key limitations include the exclusive reliance on the Scopus database, which may overlook relevant studies in non-indexed journals, and the predominance of secondary data, which might not capture the nuanced effects of ESG practices. Additionally, heterogeneity in ESG metrics complicates cross-study comparisons, highlighting the need for more standardised scoring systems. The findings underscore significant research gaps, particularly the need for cross-country and sector-specific studies, and advocate for methodological advancements such as mixed methods and longitudinal approaches to better understand ESG’s long-term impacts. Implications for practice include the necessity for companies to tailor ESG strategies to their specific contexts and for policymakers to promote standardised ESG disclosures. This review provides a foundation for future research to explore more nuanced, context-aware approaches to ESG, thereby advancing its role in shaping corporate valuation in accounting and organizational studies.